Quantitative Proteomics Reveal That Metabolic Improvement Contributes to the Cardioprotective Effect of T89 on Isoproterenol-Induced Cardiac Injury - Wei, Xiao-Hong; Guo, Xiao; Pan, Chun-Shui; Li, Huan; Cui, Yuan-Chen; Yan, Li; Fan, Jing-Yu; Deng, Jing-Na; Hu, Bai-He; Chang, Xin; He, Shu-Ya; Yan, Lu-Lu; et al. (Frontiers in Physiology, 2021)
Background: T89, a traditional Chinese medicine, has passed phase Ⅱ, and is undergoing phase Ⅲ clinical trials for treatment of ischemic cardiovascular disease by the US FDA. However, the role of T89 on isoproterenol (ISO)-induced cardiac injury is unknown. The present study aimed to explore the effect and underlying mechanism of T89 on ISO-induced cardiac injury. Methods: Male Sprague-Dawley rats received subcutaneous injection of ISO saline solution at 24 h intervals for the first 3 days and then at 48 h intervals for the next 12 days. T89 at dose of 111.6 mg/kg and 167.4 mg/kg was administrated by gavage for 15 consecutive days. Rat survival rate, cardiac function evaluation, morphological observation, quantitative proteomics and Western blotting analysis were performed. Results: T89 obviously improved ISO-induced low survival rate, attenuated ISO-evoked cardiac injury, as evidenced by myocardial blood flow, heart function and morphology. Quantitative proteomics revealed that the cardioprotective effect of T89 relied on the regulation of metabolic pathways, including glycolipid metabolism and energy metabolism. T89 inhibited the enhancement of glycolysis, promoted fatty acid oxidation, restored mitochondrial oxidative phosphorylation by regulating Eno1, Mcee, Bdh1, Ces1c, Apoc2, Decr1, Acaa2, Cbr4, ND2, Cox 6a, Cox17, ATP5g, and ATP5j, thus alleviated oxidative stress and energy metabolism disorder and ameliorated cardiac injury after ISO. The present study also verified that T89 significantly restrained ISO-induced increase of HSP70/HSP40, and suppressed the phosphorylation of ERK, further restored the expression of CX43, confirming the protective role of T89 in cardiac hypertrophy. Proteomics data are available via ProteomeXchange with identifier PXD024641. Conclusions: T89 reduced mortality and improves outcome in the model of ISO-induced cardiac injury and the cardio protective role of T89 is correlated with the regulation of glycolipid metabolism, recovery of mitochondrial function, and improvement of myocardial energy.